An application of possibilistic programming to production sequencing of mining parcels. Issue 2 (3rd April 2017) - Kumral, Mustafa; Sari, Yuksel Asli
Abstract: The mineral industries have recently experienced low commodity prices and escalating operational costs. This forces mining companies to find more efficient and productive ways to operate mines. The production sequence of mining blocks significantly affects the profitability of a mining project. Under capacity and access constraints, high quality blocks are forced to be produced during earlier periods to take advantage of the time value of money. However, financial and quality characteristics (e.g. grades, ore and waste tonnages of a block, ore prices) are imprecise at the planning stage. This research aims to address the uncertainties associated with grade and financial parameters so as to obtain a robust solution. Within this scope, the sequencing problem of mining parcels is formulated as a multi–objective optimization problem in fuzzy form, and subsequently is converted to a maximin (maximize the minimum) formulation. This formulation is then solved using a mixed integer programming solver. Two case studies show that the proposed fuzzy possibilistic model can generate an efficient compromise solution while considering uncertainties.